The challenges of the application of gender mainstreaming in rural communities : A case study of the water resources management in Mogodi village,Limpopo Province. - Ramoroka, Tlou Millicent (My University, 2010)
Gender equality in local water governance is currently envisaged as a necessary aspect for achieving efficient, effective and sustainable water resources management. Based on the premise that men and women exhibit socially and culturally determined differences in behavior, roles and responsibilities, the Gender Mainstreaming Strategy holds that gender concerns in water resources management, including in all decisions regarding planning, design, location, operation and maintenance have to be based on the recognition of their differences. However, giving the pragmatic effect on the Gender Mainstreaming Strategy within the Water Resources Management Sector has met with many challenges relating to structural issues, sustainability, the commitment of actors involved, and the whole range of aspects of attitudinal change, both at individual and collective levels. The study investigates the challenges involved in the application of the Gender Mainstreaming Strategy within the Water Resources Management Sector in the rural community of Mogodi Village in Limpopo Village. The study argues that the challenges involved in the application of the Gender Mainstreaming Strategy leads to virtual mismanagement of the water resources within rural communities as attested to by the Mogodi Village. The survey results from Mogodi Village proved that gender mainstreaming was not fully applied within the water resources management. Women do not have access to all the positions in the water committee and furthermore, they are not always consulted and if they get the chance to raise their concerns, they are not always taken into consideration. Additionally, the patriarchal tradition within the village has a great impact on the application of the Gender Mainstreaming Initiatives. Some of the principles of this tradition are that women are household caregivers and men are leaders. The roles that women perform within their homesteads do not allow them time to participate in the water resources management. This leaves the water resources management roles in the hands of men in the village. The study therefore concludes that the genuine benefits of the Gender Mainstreaming Strategy in the water resources management would not be realised as long as the context within which it is applied remains traditional in terms of the gender status quo.
Thesis (M.A.) (Development management) --University of Limpopo, 2010.
Keywords: Gender mainstreaming; Rural communities; Water resource management; 553.7 RAM; Water resource management; Water Report